2021
DOI: 10.1097/mej.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

A quick modified early warning score for triaging medical patients at admission

Abstract: Early warning scores (EWS) are clinical rules, based on physiological variables, designed to identify patients at risk of clinical deterioration and death [1,2]. The most popular is the modified early warning score (MEWS) [3], comprised of five items (heart and respiratory rate, systolic blood pressure, fever and state of consciousness); the higher the derangements, the higher the risk of deterioration.We and others [4][5][6] tested the hypothesis that a single MEWS, computed at admission, can serve to stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although statistically appropriate, the results provided by multivariate logistic regression analysis, AUC and net benefit analyses can be challenging to interpret by clinicians, because the results are too abstract to directly apply in clinical practice. The benefit of presenting a sequential post-test mortality risk is that it provides the actual mortality risk per category, which is intuitive to interpret [ 16 ]. In the univariate and AUC analysis, we found that the performance on 30-day mortality of suPAR and procalcitonin are in line with other studies [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although statistically appropriate, the results provided by multivariate logistic regression analysis, AUC and net benefit analyses can be challenging to interpret by clinicians, because the results are too abstract to directly apply in clinical practice. The benefit of presenting a sequential post-test mortality risk is that it provides the actual mortality risk per category, which is intuitive to interpret [ 16 ]. In the univariate and AUC analysis, we found that the performance on 30-day mortality of suPAR and procalcitonin are in line with other studies [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, we considered two types of score: generic scores-systems (NEWS2, MREMS, or ViEWS) applicable across all acute illnesses [17][18][19][20], which included RAPS, derived from the Acute Physiology and Chronic Health Evaluation II and customized for use in ambulance services; specific scores for particular conditions [21], such as CART, used in cardiovascular pathology, TEWS for trauma and injuries pathologies, and qSOFA, employed for patients with presumed infection in order to identify misleading cases of sepsis [22].…”
Section: Main Findingsmentioning
confidence: 99%